Pendidikan Pemahaman Islam Nusantara - Surawardi Surawardi (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2021)
The emergence of the term Islam Nusantara invites many pros and cons from the community, including from academics. Islam that was revealed is Islam for all Muslims everywhere from this hemisphere. If it is labelled as Nusantara, it will give the impression of a partial understanding of Islam from among the Muslims themselves. There is nothing wrong with the term "Islam Nusantara". For this reason, it is necessary to have an educational understanding of the concept of Nusantara Islam which is lifted from local wisdom for Islam in the archipelago, namely Islam for the people of Indonesia. The definition of Islam Nusantara itself is Islam Ahlussunnah Wal Jama'ah which is practised, preached and developed according to the characteristics of society and culture in the archipelago by its preachers. One of the goals is to anticipate and fortify the people from radicalism, liberalism, Shi'ism, Wahhabism and other ideas that are not in line with Ahlussunnah Wal Jama'ah. There are two ways in education to understand Islam Nusantara, namely through: Education of Tolerance Values Between Fellow Muslims and Education of Tolerance to Tradition or Culture. Keywords: Education and values, Islam Nusantara.